BATTLE OF CULTURES: TRANSLATING FIGURATIVE INSULTS IN REMY SYLADO’S CA-BAU-KAN - Jaya, Doni (International Review of Humanities Studies, 2023)
Translating figurative insults is one of the challenging features of literary translation because these expressions are often culture-bound and produce specific effect. This study seeks to propose a translation produced using predominantly foreignizing approach in an attempt to preserve the original effects, connotations, and nuances of the source text and to examine the extent to which foreignization and domestication can work together when used to deal with certain text types. The source text is taken from Remy Sylado’s novel Ca-Bau-Kan: Hanya Sebuah Dosa, particularly figurative verbal insults between several characters because of their offensive and hilarious double-effect unique to the Betawi culture of Indonesia. Analysis found 9 non-substitutions, 14 partial substitutions, and 7 total substitutions of figurative images, which reflects the translator’s foreignizing tendency. However, there are also some domesticating strategies in order to avoid gross awkwardness and/or loss of effect due to target language constraints and the connotative neutrality of perfect literal equivalents. This study demonstrates that the foreignization approach can be applied with little domestication when the source text shows high originality and the target language has the right linguistic devices to accommodate it.